Use of active methodologies in the Nursing graduate course: an opportunity to overcome the traditional teaching model (Research, Society and Development, 2021)
Objective: To understand the use of active methodologies in the Nursing graduate course. Methodology: This is an integrative literature review that had as its guiding question “What are the benefits that the use of active methodologies in the Nursing graduate course brings to overcome the traditional teaching model?”. The review was constructed through the Biblioteca Virtual em Saúde and the Portal de Periódicos da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior, using the descriptors "metodologias ativas", "ensino" and "Enfermagem". Results: With regard to the topics covered by the articles selected for discussion, there was a predominance of debates about the teaching-learning process, academic tutoring practices, teaching difficulties, teacher planning and student performance. As for the active methodologies commonly used in the studies, the problem-based learning, the problematizing methodology and the analysis of the active methodologies in general stood out. Final considerations: It is inferred that the use of active methodologies in the Nursing course leads to the formation of a critical-reflective nurse. Through them, it becomes possible for the student to become aware of his qualities and limitations in the search for better learning strategies. The use of these methodologies breaks with the traditional model of teaching, used for so long in educational institutions.